Ir study of monocalcium aluminate-organic acid compounds - Ali M.M.; Narang K.K.; Singh V.K. (My University, 2025)
The nature of formation of compounds between monocalcium aluminate and organic acids such as salicylic, anthranilic and sulphanilic acid taken in the ratio of 1: 1, 10: 1 and 100: 1 respectively was studied by infra-red spectroscopy. Sallcvlic and anthranilic acids deprotonate to form resonanc∼ stabilized chelate structures with hydrated alumina while sulphanillc acid deprotonates to form bridged complexes in the cementitious phase. © 1980 Taylor & Francis Group, LLC.